Chapter Strategie di relativizzazione in russo - Milani, Sara (Firenze University Press, 2022)
This article is dedicated to relativization in contemporary Russian and provides an overview of the main Russian morphosyntactic relativization strategies (Cinque 2013). The study describes the typological variety of Russian RCs, using data taken from the National Corpus and tested with native speakers’ judgments. Three criteria have been adopted to examine Russian RCs: the cross-linguistic linear orders of RC and Noun Head (Dryer 2005), the presence of a resumptive pronoun in the relativization site (Lavine 2003) and, finally, the inflectional completeness of the RC (finite/ non-finite RCs).